2015
DOI: 10.1038/ncomms9512
|View full text |Cite
|
Sign up to set email alerts
|

Membrane stiffening by STOML3 facilitates mechanosensation in sensory neurons

Abstract: Sensing force is crucial to maintain the viability of all living cells. Despite its fundamental importance, how force is sensed at the molecular level remains largely unknown. Here we show that stomatin-like protein-3 (STOML3) controls membrane mechanics by binding cholesterol and thus facilitates force transfer and tunes the sensitivity of mechano-gated channels, including Piezo channels. STOML3 is detected in cholesterol-rich lipid rafts. In mouse sensory neurons, depletion of cholesterol and deficiency of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(147 citation statements)
references
References 55 publications
8
129
3
Order By: Relevance
“…This differs from previously identified Piezo1 regulatory proteins including polycystein-2 (PC-2) and stomatin-like protein-3 (STOML3), which appears to regulate Piezo function through indirectly altering the membrane curvature or stiffness [34][35][36] . We thus went on to test how SERCA2 interaction could regulate Piezo1.…”
Section: Identification Of Sercas As Interacting Proteins Of Piezo1contrasting
confidence: 90%
“…This differs from previously identified Piezo1 regulatory proteins including polycystein-2 (PC-2) and stomatin-like protein-3 (STOML3), which appears to regulate Piezo function through indirectly altering the membrane curvature or stiffness [34][35][36] . We thus went on to test how SERCA2 interaction could regulate Piezo1.…”
Section: Identification Of Sercas As Interacting Proteins Of Piezo1contrasting
confidence: 90%
“…Whether the low-threshold regime depends on specific interactions between the channel and the ECM protein, or reflects more efficient stretching of the membrane mediated by adhesion of a “sticky” cantilever to the cell surface remains to be determined. Taken together, the results from the studies by Poole et al [50], Qi et al [51], and Gaub and Miller [52] suggest that the response of Piezo1 to outside-in mechanical forces can be modulated by cytoskeletal tethers and scaffold proteins.…”
Section: Effects Of the Cytoskeleton On Piezo1 Activationmentioning
confidence: 86%
“…Currents were observed with ~10nm pillar deflection, as compared to 100–1000nm deflections in the absence of STOML3. Subsequently, Qi et al showed that STOML3-mediated sensitization of Piezo1 depends on cholesterol binding, and proposed that STOML3 influences membrane mechanics and facilitates force transfer to the channel protein [51]. …”
Section: Effects Of the Cytoskeleton On Piezo1 Activationmentioning
confidence: 99%
“…It is easily imaginable that mechanically-activated channels like Piezo could be affected by the surrounding membrane properties. Their activity have already been shown to be highly dependent on the membrane stiffening [58] and thus the membrane chol content, but also on the level of fatty acid saturation [59]. Moreover, new insights in Piezo1 structure evidenced a bend in its transmembrane section [60], whose stabilization energy might be partly compensated by the surrounding lipids.…”
Section: Lipid Domains As Modulators Of Piezo1 and Pmca Membrane Locamentioning
confidence: 99%